Effect of katuk leaf meal and mulberry leaf meal in the diet on size and mineral content of tibia bone of laying quail - Hermana W; Toharmat T; Sumiati .; Manalu W (Indonesian Center for Animal Research and Development (ICARD), 2013)
The objectives of this research was to study tibia bone mineral content and blood profil of laying quail offered control diet (P0); diet with 10% katuk leaf meal /KLM (P1); diet with 10% mulberry leaf meal/MLM (P2); and diet with 5% KLM+5% MLM (P3). A completely randomized design using 4 treatments, 5 replications, and 2 quails of 17 weeks of age in each experimental unit replication was used in this experiment. The data were analyzed using analysis of variance and Duncan test. Parameters observed were tibia bone mineral content. The result showed that quail tibia bone weight and percentage of tibia bone weight were not affected by treatment, but diametre of tibia bone from quail fed mixture of KLM+MLM in the diet shorter (P < 0.05) than that of the other treatment. It was concluded that KLM and MLM can be used in the diet of laying quail up to 10% without affected the tibia bone mineral content. Key Words: Katuk Leaf Meal, Laying Quail, Mulberry Leaf Meal, Tibia Bone.